The king's living image : the culture and politics of viceregal power in colonial Mexico - Cañeque, Alejandro (New World in the Atlantic world., 2004)
Taking a fresh look at the political culture of the Spanish monarchy, this work investigates the politics of imperial rule & viceregal power in 17th century Mexico as well as the construction of the colonial state. It challenges long held perspectives on colonial Spanish America.